Forest Diversity Reduces the Prevalence of Pathogens Transmitted by the Tick Ixodes ricinus - Bourdin, Audrey; Bord, Severine; Durand, Jonas; Galon, Clemence; Moutailler, Sara; Scherer-Lorenzen, Michael; Jactel, Herve (Frontiers in Ecology and Evolution, 2022)
Tick-borne diseases represent the majority of vector-borne human diseases in Europe, with Ixodes ricinus, mostly present in forests, as the main vector. Studies show that vertebrate hosts diversification would decrease the prevalence of these pathogens. However, it is not well known whether habitat diversity can have similar impact on ticks and their infection rates. We measured the presence and abundance of different stages of I. ricinus, and the prevalence of associated pathogens in a large-scale forest experiment in which we manipulated tree diversity and moisture level. We showed that larval abundance was influenced by tree species identity, with larvae being more present in pine plots than in oak plots, while nymph abundance increased with canopy tree density. The proportion of Borrelia bugdorferi s.l.-infected nymphs decreased with increasing tree diversity. Our findings suggest that tree overstorey composition, structure and diversity, can affect tick abundance and pathogen prevalence. They support the idea that forest habitats may have “diluting” or “amplifying” effects on tick-borne diseases with direct relevance for human health.